The impact of shelter-in-place during the COVID-19 pandemic on social support for mental health recovery: A prescribing-oriented qualitative study of patient perspectives. - A Song; T Chao; B Harris; H Hsin (PLoS ONE)
The COVID-19 pandemic created unprecedented challenges for social connectivity and mental health, especially during mandated shelter-in-place periods. For patients engaged in mental health treatment, the social impact of their shelter-in-place experience remains an area of active investigation. This is particularly relevant in the context of social prescribing, a growing area of clinical intervention where healthcare providers actively refer patients to local social resources or activities to enhance mental health and wellbeing. Here, we investigated patient perspectives on their social supports during shelter-in-place, with an eye toward informing future social prescribing and counseling steps that mental health clinicians can take to foster social resiliency of patients. We conducted semi-structured phone interviews with 12 participants receiving mental health treatment at Kaiser Permanente San Jose Adult Psychiatry clinics. Interviews were transcribed and analyzed for themes. The sample consisted of 8 female and 4 male participants between the ages of 21 to 44, who received services including outpatient medication management, outpatient therapy, and/or outpatient group therapy. Analysis revealed two thematic categories that participants identified: (A) Specific ways that shelter-in-place impacted their social experience and (B) specific types of social relationships that participants felt were important to their mental health and wellbeing. In the first category, thematic factors that affected the social experience included (1) COVID-19-related health concerns, (2) participants' baseline socialization patterns (degree of introversion/extroversion) and (3) the use of online and social media communication channels. For the second category of themes, specific functions of social relationships identified included those centered around (a) instrumental support, (b) emotional support, (c) community connection. Many relationships served more than one function during shelter-in-place, and many participants cited perceived community connection as a particularly important element in their mental health recovery. These themes highlight key contributors to the social experience of the shelter-in-place period for individuals in mental health recovery and inform future ways that clinicians can structure social prescribing practices to better assist the needs of patients.